The Influence of Auditor Competence and Integrity on Audit Quality with the Implementation of Quality Assurance as a Moderating Variable - Perdana, Taufan Aditya; Wahidahwati, Wahidahwati; Priyadi , Maswar Patuh (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The audit profession plays a crucial role in ensuring the accuracy and reliability of financial statements, which is increasingly important in a globalized economy. However, scandals involving audit failures, especially within government institutions, have led to a decline in public trust. Specific Background: In Indonesia, the Directorate General of Customs and Excise (DGCE) performs compliance audits that are vital to state revenue. The audit quality within such institutions is contingent upon the auditors’ competence and integrity, as these factors are essential for comprehensive and fair audits. Knowledge Gap: Despite existing research, there is inconsistency in the literature regarding the impact of auditor competence and integrity on audit quality, and the role of quality assurance as a moderating variable remains unexplored​​. Aims: This study aims to analyze the influence of auditor competence and integrity on audit quality and to determine whether the implementation of quality assurance moderates these relationships​​. Results: The study finds that both auditor competence and integrity positively affect audit quality, while quality assurance independently enhances audit quality. However, quality assurance does not moderate the relationship between auditor competence or integrity and audit quality​​. Novelty: This research is novel as it integrates quality assurance as a moderating variable, a factor not previously examined in similar studies​​. Implications: The findings suggest that the DGCE should focus on enhancing auditors’ competence and integrity while maintaining robust quality assurance practices to ensure high audit quality, thereby restoring public confidence​​.